Types of the herbarium “Julián Acuña Galé”, University of Camagüey, Cuba - Julio Cesar Rifa Tellez (Universidad Central "Marta Abreu" de Las Villas, 2021)
nformation is compiled referring to the type specimens kept in the herbarium "Julián Acuña Galé", of the University of Camagüey "Ignacio Agramonte Loynaz", Cuba. The existence of 17 specimens that typify the names of 12 taxa (eight species, two subspecies and two forms), belonging to 10 genera and four families, is disclosed. Seven are holotypes and 10 isotypes. The presence in this herbarium of three of the latter is revealed for the first time, while another three do not have duplicates in other collections.